2018
DOI: 10.1016/j.jgo.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and impact of grade three or four toxicities of novel agents on outcomes of older patients with chronic lymphocytic leukemia and non-Hodgkin lymphoma (alliance A151611)

Abstract: Objective Older patients with cancer suffer from chemotherapy-related toxicities more frequently than younger patients. As novel agents are being used more commonly in chronic lymphocytic leukemia (CLL) and non-Hodgkin lymphoma (NHL), toxicities of these agents in older patients have not been well studied. Further, impact of these toxicities on outcomes in the elderly is unknown. This study aimed to answer both questions. Patients and Methods We reviewed 14 Alliance for Clinical Trials in Oncology trials tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is also known that CLL risk increases and the antioxidant capacity of the human body decreases with age. Moreover, it has been reported that CLL and NHL patients ≥65 years encounter more toxicities than younger patients after chemotherapy due to reduced antioxidant capacity (43). Based on the above and our findings, we suggest that the Q192R polymorphism of the fundamental antioxidant PON1 gene, which results in the reduction of the antioxidant PON1 activity, along with the accumulation of genotoxic compounds due to the onset of CLL in advanced age, may play a role in CLL development and in the formation of CLL chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that CLL risk increases and the antioxidant capacity of the human body decreases with age. Moreover, it has been reported that CLL and NHL patients ≥65 years encounter more toxicities than younger patients after chemotherapy due to reduced antioxidant capacity (43). Based on the above and our findings, we suggest that the Q192R polymorphism of the fundamental antioxidant PON1 gene, which results in the reduction of the antioxidant PON1 activity, along with the accumulation of genotoxic compounds due to the onset of CLL in advanced age, may play a role in CLL development and in the formation of CLL chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…These issues include quality of life of older patients during cancer therapy; older patients' self-reported cognitive function over time during cancer treatment; social support and its ramifications during the cancer journey; rates of chemotherapy-induced neuropathy in older patients; tolerating capecitabine within the context of renal dysfunction; patient preferences with respect to adjuvant chemotherapy; defining the role of doublet, platinum-based chemotherapy in older patients with lung cancer; the identification of risk factors for toxicity in older patients with hormone receptor-positive breast cancer; reasons for time-to-treatment failure in older versus younger patients with cancer; the impact of body weight-based chemotherapy dosing on cancer outcomes in older patients with breast cancer; using placebo to show that adverse event reporting is comparable in older and younger patients; details on the trajectory of frailty among older patients; the value and limitations of using ePrognosis to estimate 2-year all-cause mortality in older women with breast cancer; trends in accrual of older women with breast cancer to clinical trials; and an exposition of the role of older-patient-specific trials and their importance in geriatric oncology care [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Understanding Clinical Care Issues In Older Patients With Camentioning
confidence: 99%
“…In the months that followed, I worked with one of my former fellows, the statistics team, and the rest of the committee members to complete the study that was subsequently published in the Journal of Geriatric Oncology [3]. We uncovered the frequency of toxicities in older patients with lymphoma receiving biologic therapies.…”
mentioning
confidence: 99%